Why presidents fail - Pious, Richard M. 1944- (Rowman & Littlefield, 2008)
Why Presidents Fail takes a fresh look at cases that became defining events in presidencies from Dwight D. Eisenhower through George W. Bush and uses these cases to draw generalizations about presidential power, authority, rationality, and legitimacy. Rather than assigning blame for past failures, this book focuses on why presidents fail and how future presidents might avoid making these same disastrous mistakes.